Use Pareto Chart to diagnose the level of quality of municipal services - حافظ, عبد الناصر علك; سعيد, فاضل محمد (Journal of Economics and Administrative Sciences, 2020)
The aim of the study is to study the quality of services in a sample of the municipalities of Baghdad governorate and identify the deviations in their operations and provide solutions to address the causes of deviations. The research field aims at the same activity related to municipal services and their quality and analysis using some tools for continuous improvement to identify the authorities responsible for the delay and quality of services. In the future, the importance of research is shown by the use of these tools and their use and their application to the data of the directorates (sample of the study) to diagnose and treat problems, especially that they include statistical methods that are clear and easy to understand the method of the stratified sample was used to represent the research society to reach real results that represent the society more precisely. The research used a case study methodology to reach a comprehensive picture of the research community represented by the municipal administration of Baghdad governorate. Four samples were used for the first research. , The second was the Municipality Directorate of Abu Ghraib, the third was the municipality of Mahmudiyah, and the fourth was the Nahrawan Municipality Directorate. The researcher used a questionnaire to express the views of the research sample of (50) engineers and technicians from the directorates (sample of the study), representing more than 25% Data collected through the examination lists, records and documents, the survey form, and the workshops conducted during the period of research. The research reached a number of main and secondary reasons responsible for the delay and quality of municipal services in the research sample, (Sewage networks, drinking water plants, and conflicts with projects).